Anti-Group B Streptococcus antibody in infants born to mothers with human immunodeficiency virus (HIV) infection. Issue 5 (29th January 2015) - Le Doare, Kirsty; Allen, Lauren; Kampmann, Beate; Heath, Paul Trafford; Taylor, Stephen; Hesseling, Anneke C.; Gorringe, Andrew; Jones, Christine Elizabeth
Highlights HIV-infected women have lower anti-GBS surface binding antibody concentrations than uninfected controls with reduced antibody-mediated deposition of complement C3b/iC3b onto GBS bacteria. HIV-exposed, uninfected infants have a lower concentration of antibody binding to the surface of GBS bacteria as well as a reduction in antibody-mediated deposition of complement C3b/iC3b onto the surface of GBS strains at birth compared to HIV-unexposed infants. As a result, HIV-exposed uninfected infants may be at increased risk of early and late onset GBS disease compared to unexposed infants.